Perception of pregnant women towards early antenatal visit in Fiji: a qualitative study - Renita Maharaj; Masoud Mohammadnezhad (BMC, 2022)
Abstract Background Antenatal Care (ANC) is an opportunity to provide care to prevent potential maternal and new born mortality and morbidity and reduce new born mortality and morbidity. There has been an increase in the number of women receiving early ANC over the last two decades, however, in many developing regions such as Fiji, women are still delaying initiation of ANC. Therefore, the aim of this study is primarily to explore reasons for delayed initiation of ANC appointments and to explore knowledge and perception of pregnant mothers towards early antenatal appointments in Fiji. Methods The study uses a qualitative approach. Data was collected among pregnant women more than 18 years of age after 12 weeks of gestation attending their first ANC clinic at the Ba Mission Hospital (BMH) from February 28 to April 2, 2020. Heterogenous purposeful sampling method was used to select 25 pregnant women for the study. A semi-structured open-ended questionnaire was used for face to face in-depth interviews. Data was analyzed manually using thematic content analysis after verbatim transcription of the interviews. Results The mean age of the participants was 25.8 ± 5.9 years (age range of 19-40 years). The average gestational age of those making a booking for a consultation was 5.4 ± 1.4 months with a range of 4 to 8 months. The majority of women were multigravida (64%) and multiparous (40%). The main themes that emerged from the study were: i) perception of early ANC booking; ii) perceived barriers of early ANC booking and; iii) enabling factors of early ANC booking. Even though pregnant women have a good knowledge of when to initiate ANC, the practice of early booking was influenced by many other factors. Conclusions The results of this study highlight the need to change the current booking system. Efforts are needed to attract the hard-to-reach women through outreach visits and increased communication between health care workers and the community with the use of community resources such as community health workers and traditional birth attendants. The media should be used to create awareness on timing and importance of early ANC visits at a community level.